Transcriptional Regulation of Brassinosteroid Accumulation during Carrot Development and the Potential Role of Brassinosteroids in Petiole Elongation - Que, Feng; Wang, Guang-Long; Xu, Zhi-Sheng; Wang, Feng; Xiong, Ai-Sheng (Frontiers in Plant Science, 2017)
It is widely known that brassinosteroids (BRs) are involved in various physiological processes during plant growth and development. Roles of BRs have been reported in many plants. However, relevant report is yet not found in carrot. Carrot is a nutrient-rich vegetable from the Apiaceae family. Here, we measured the bioactive contents of BRs at five successive stages and analyzed the expression profiles of genes involved in BR biosynthesis, signaling pathway and catabolism. We found that most biosynthesis regulated genes had higher expression level at the first development stage of carrot and the catabolism gene BAS1/CYP734A1 had significantly high expression level at the first stage in carrot roots and petioles. In addition, we treated carrot plants with exogenous 24-epibrassinolide (24-EBL) and examined the morphological changes after treating. Compared with control plants, carrot plants treated with 24-EBL had higher plant height, more number of petioles and heavier aboveground weight. The expression levels of DcBRI1, DcBZR11, and DcBSU1 in the petioles were significantly up-regulated by treating with exogenous 24-EBL. The expression profiles of DcCYP734A1 were all significantly up-regulated in the three organs when treated with 0.5 mg/L 24-EBL. The elongation of carrot petioles can be promoted by treating with exogenous 24-EBL. These results indicate that BRs playing potential roles during the growth and development of carrot.